PERANCANGAN MEDIA PEMBELAJARAN MOBILE LEARNING MATERI MACAM-MACAM BATUAN PADA MATA PELAJARAN GEOGRAFI BERBASIS WEB MOBILE - Yolanda Sari, Noca; Agustiyan, Dimas; Puastuti, Dwi (JMPA (Jurnal Manajemen Pendidikan Al-Multazam), 2021)
Smartphones are information technology devices that are no longer an option, but have become a necessity in order to improve the learning process. Smartphone devices are also equipped with an operating system like a computer, smartphones can implement various forms of multimedia such as computers, except that they have high mobility and can be operated more effectively. Humans as technology developers who are carried out continuously from time to time have always increased, in the field of education. One of the uses of smartphone technology in educational activities is that it is used as a learning medium such as in geography subjects, materials of various kinds of rocks. However, in senior high school (SMA) class X, for geography subjects. The learning media used is very lacking, the teacher only uses conventional learning, with the lecture method so that it makes it difficult for students to understand the material. The existence of these problems, the researcher wants to make mobile learning media that will be used by students by using smartphones as a device to access information in the form of a mobile web.